PENGARUH KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN DAN KUALITAS LABA TERHADAP NILAI PERUSAHAAN (STUDI PADA EMITEN MANUFAKTUR DI BURSA EFEK INDONESIA) - Iwan Efriandy (Universitas Indo Global Mandiri, 2022)
The purpose of this study was to determine the effect of institutional ownership, firm size and earnings quality, either simultaneously or partially with respect to the issuer company in manufacturing in Indonesia Stock Exchange (IDX) with the observation period from 2006 to 2009. This type of study is a hypothesis testing study with a sample of purposive sampling method.Target population of this study is the issuer of manufacturing in Indonesia Stock Exchange (BEI), which has complete data related to institutional ownership, assets, receivables, liabilities, sales, net income and operating cash flow. The research sample consists of 149 observations. To test the effect of institutional ownership, firm size and earnings quality both simultaneously and partially on the company used multiple linear regression models.The results showed: (1) institutional ownership has a positive effect on firm value, but the effect is very small, (2) the size of the company's negative effect on the value of the firm and its influence is small, (3) a positive effect on earnings quality and firm value, (4) simultaneously institutional ownership, firm size and earnings quality significantly influence the value of the company.